R&D Spillovers with Endogenous Absorptive Capacity: Lessons for Developing Countries - Chankwon Bae (East Asian Economic Review (EAER), 2016)
This paper analyzes the role of absorptive capacity in R&D spillovers through strategic R&D investments in a game-theoretic framework. In the model, a firm's effective R&D is composed of idiosyncratic R&D, which produces its own innovations, and identical R&D, which improves absorptive capacity. The model shows that in the presence of absorptive capacity firms have a tendency to underinvest (overinvest) in idiosyncratic (identical) R&D relative to the social optimum. As the spillover becomes larger, firms decrease their own R&D while they become more inclined towards strategic exploitation of rivals' efforts. Since the former effect overpowers the latter, the total amount of R&D decreases as the spillover increases. This is socially undesirable, providing a potential justification for a governmental subsidy for idiosyncratic R&D and a tax on identical R&D. The findings may have important implications for newly industrialized or emerging countries that consider a redirection of national R&D policy and intellectual property rights (IPR) regime.
Keywords: L13; O31; O32; O38; 330; Absorptive Capacity; R&D; Spillovers